Self-rated health (SRH) partially mediates and associations between personality traits and life satisfaction in older adults - Kang, Weixi; Malvaso, Antonio (Frontiers in Psychology, 2023)
It is established that personality traits contribute to life satisfaction but why they are connected are far less understood. This research report tested if self-rated health (SRH) which is one’s subjective ratings of their health and has a high predictivity of actual health mediates the associations between the Big Five model of personality and life satisfaction in a cohort (N=5845) of older adults from the UK. By using Pearson’s correlation analysis and mediation analysis, the current research reported positive correlations between Agreeableness, Openness, Conscientiousness, and Extraversion, SRH, and life satisfaction. However, Neuroticism was negatively correlated with SRH and life satisfaction. The main findings were that SRH partially mediates the associations between all traits in the Big Five and life satisfaction in older adults. This study began novel exploration on if SRH could explain the connections between the Big Five and life satisfaction. Results revealed SRH could partially explain these associations in all traits. These results may offer additional support to recently developed integrated account of life satisfaction, which argues that there are no single determinants of life satisfaction. Rather, life satisfaction is made up by many factors including but not limited to personality and health.